2006
DOI: 10.1093/sleep/29.7.927
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Fluorodeoxyglucose Positron Emission Tomography Study in Healthy Adults Reporting Dream-Enactment Behavior

Abstract: These preliminary findings suggest that cognitively normal persons with DEB have reduced CMRgl in brain regions known to be metabolically affected by DLB, supporting further study of DEB as a possible risk factor for the development of DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…As summarized in the Table, cross-sectional studies in patients with iRBD have shown that a significant proportion of them have detectable abnormalities on measures of smell testing, 6469 color vision and discrimination, 17, 69 cardiac autonomic activity, 17, 70, 71 cardiac (123)I-metaiodobenzylguanidine (MIBG) imaging, 7274 motor and gait functioning, 17 neuropsychological testing, 75–78 electroencephalography (EEG), 7981 transcranial sonography (TCS), 15, 22, 66, 68, 82 magnetic resonance imaging (MRI)/magnetic resonance spectroscopy (MRS), 8386 single photon emission computed tomography (SPECT), 87, 88 dopamine transporter imaging using SPECT, 15, 16, 22, 64, 66, 8991 fluoro-deoxyglucose positron emission tomography (FDG-PET), 92, 93 and dihydrotetrabenazine (DTBZ) PET. 94 .…”
Section: Longitudinal Assessment Of Irbd Subjects – Testing the Braakmentioning
confidence: 99%
“…As summarized in the Table, cross-sectional studies in patients with iRBD have shown that a significant proportion of them have detectable abnormalities on measures of smell testing, 6469 color vision and discrimination, 17, 69 cardiac autonomic activity, 17, 70, 71 cardiac (123)I-metaiodobenzylguanidine (MIBG) imaging, 7274 motor and gait functioning, 17 neuropsychological testing, 75–78 electroencephalography (EEG), 7981 transcranial sonography (TCS), 15, 22, 66, 68, 82 magnetic resonance imaging (MRI)/magnetic resonance spectroscopy (MRS), 8386 single photon emission computed tomography (SPECT), 87, 88 dopamine transporter imaging using SPECT, 15, 16, 22, 64, 66, 8991 fluoro-deoxyglucose positron emission tomography (FDG-PET), 92, 93 and dihydrotetrabenazine (DTBZ) PET. 94 .…”
Section: Longitudinal Assessment Of Irbd Subjects – Testing the Braakmentioning
confidence: 99%
“…These findings may help further explain the clinical differences between RBD and TSD. Cerebral hypometabolism in occipitoparietal, paralimbic, and anterior temporal cortices has been reported on PET scans of patients with RBD 29,30 In a study of combat-related PTSD with patients who reported DNB, cerebral hypermetabolism was detected in brainstem regions, such as the midbrain reticular formation, locus ceruleus, and the pedunculopontine tegmentum, as well as regions involved in the threat response (e.g., amygdala, dorsal cingulate, and hippocampus) during wakefulness and REM sleep. 31 Hyperactivity in these neuroanatomical regions during REM may result in RWA and DNB, including dream enactment behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, imaging studies show reduced blood flow and glucose metabolism in frontal, parietal, and temporal regions in RBD (Shirakawa et al, 2002;Caselli et al, 2006;Mazza et al, 2006). These areas also have reduced EEG activity during waking and NREM in RBD patients.…”
Section: Inhibition and Eeg Slowing In Rbdmentioning
confidence: 99%